Current Position of India’s Foreign Trade with China (The Changes Taking Place) - Kansal, Mani (Journal of Commerce and Trade, 2008)
We analyze causality relationships between industry and foreign trade in two major areas of the world economy: India, China for the period 2002-07, and found that the effect of imports is usually positive and significant to favour industrial and non-industrial development, from a mixed approach to economic growth which has into account demand and supply sides. The goals of achieving an all round economics self-sufficiency transforming the back word agrarian Indian economy into an industrial nation and ensuring the millions a better quality of life. The pressure on Indian manufacturers to become more efficient and on the Indian government to accelerate the elimination of India’s disadvantage in infrastructure. There are vase opportunities for increasing the contents of our expert basket to china. Quantum of export and import with china has changed since 1991.